Key Factors in the Success of Virtualization of Teaching in Spanish Universities During the COVID-19 Pandemic - Alfonso Infante-Moro; Juan C. Infante-Moro; Julia Gallardo-Pérez (Springer, 2022)
The virtualization of university teaching in Spain caused by the pandemic was a success, but the urgent nature of the transition from face-to-face teaching to online teaching meant that some peculiarities that should have been taken into account were omitted. Thus, in order to find out and analyze the factors causing the success of this virtualization and take measures to address the weak points of this process as teachers may want to maintain the use of online teaching as support for their face-to-face teaching, these factors were located through a literature review and were classified according to their level of importance in this success through a causal study carried out with the methodology of fuzzy cognitive maps. The results achieved indicated the determining factors in students, involving their attitude, aptitude and predisposition, which are factors where the work of the teacher is of main relevance (as it exerts the greatest influence on these factors). For this reason, technological attitude and aptitude, teaching style, and the creation and structuring of content should be reinforced in teachers.